Optimization of an Analytical Method for Indoxacarb Residues in Fourteen Medicinal Herbs Using GC–μECD, GC–MS/MS and LC–MS/MS - Hun-Ju Ham; Syed Wasim Sardar; Abd Elaziz Sulieman Ahmed Ishag; Jeong-Yoon Choi; Jang-Hyun Hur (Separations, 2022)
Pesticide residue analysis in medicinal herbs is a challenging task because of the matrix effect and its influence on quantitative analysis despite the continuous development of several new analytical methods and instrumentations. In this study, a modified QuEChERS method was developed for the analysis of indoxacarb residue in medicinal herbs by using the conventional instrument, gas chromatography micro-electron-capture-detector (GC–μECD), and comparing it with gas chromatography–tandem mass spectrometry (GC–MS/MS) and liquid chromatography–tandem mass spectrometry (LC–MS/MS). Samples were extracted with acetonitrile and purified using an NH2 cartridge. The optimized method efficiently removes the co-extractives and offered a limit of quantification of 0.01 mg kg−1. The GC–μECD analysis results of indoxacarb in seven medicinal herbs out of fourteen species at a fortification level of 0.01 mg kg−1 showed a recovery range of 79.7–117.6%, while the rest showed recovery > 120%. Similarly, the recovery of indoxacarb by GC and LC–MS/SM were 74.1–105.9 and 73.0–99.0%, respectively, with a relative standard deviation of <20%. Matrix effects for the majority of medicinal herbs analyzed by GC–MS/MS were >±20%. Whereas the results for LC–MS/MS were <20%, which was within the acceptable range according to the SANTE/11312/2021 guidelines. Considering the performance of the method and alignment with the regulatory guidelines, LC–MS/MS is recommended for the analysis of indoxacarb in selected medicinal herbs.